Length of Menopause has a Positive Correlation with C-Telopeptide Plasma Level in Pascamenopause Women - Willy Pangestu; Eddy Suparman; Freddy Wagey (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To determine the correlation between length of menopause with C-telopeptide in pascamenopause women. Method: An analytic cross-sectional study of 29 pascamenopause women in Malalayang hospital Manado. Sampling method with consecutive random sampling. Data were analyzed with Spearman test with significance level of p